2011
DOI: 10.1063/1.3544036
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic reversal of cylindrical nickel nanowires with modulated diameters

Abstract: Anodic alumina membranes with modulated pore diameters serve as template for the preparation of magnetic nanowires. Filling the pores with Ni by electrodeposition delivers wires replicating the variation in modulation in pore diameter from 80 to 160 nm. Such structures are of interest for the observation and control of magnetic domain wall motion. Single-object characterization utilizing the magneto-optical Kerr effect magnetometry evidences a strong correlation between geometric parameters and magnetic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 47 publications
1
67
0
2
Order By: Relevance
“…To stabilize domain walls in nanowires we make use of local protrusions placed every other several micrometers, to act as potential barriers for domain walls motion. While these barriers are not sufficient to pin domain walls when the magnetic field is applied along the wire [24], we found that they are fit to prevent motion of domain walls upon dc oscillatory demagnetization with the magnetic field applied perpendicular to the wafer plane.…”
mentioning
confidence: 84%
“…To stabilize domain walls in nanowires we make use of local protrusions placed every other several micrometers, to act as potential barriers for domain walls motion. While these barriers are not sufficient to pin domain walls when the magnetic field is applied along the wire [24], we found that they are fit to prevent motion of domain walls upon dc oscillatory demagnetization with the magnetic field applied perpendicular to the wafer plane.…”
mentioning
confidence: 84%
“…Recent progress in sample growth has allowed to create free-standing nanowires which are grown perpendicular to their substrate (for example [44][45][46]. While it is outside the scope of this work to investigate these systems in detail, we comment briefly on possible analytical approximations.…”
Section: Perpendicular Nanowiresmentioning
confidence: 99%
“…1(c,e). As already noticed, modulations of diameter 16 as well as roughness or structural / anisotropy fluctuations 20 also induce a local contrast, with monopolar and dipolar feature along the wire direction, respectively. However, a closer look reveals also a transverse dark/light dipolar contrast perpendicular to the axis at DWs, diameter modulations and wire ends (Fig.…”
Section: Imagingmentioning
confidence: 81%
“…1(a-c), and was used by us to evidence again transverse walls and also for the first time Bloch-point walls by photo-emission electron microscopy 17 . Note however that, as the resulting pinning field is expected to be lower than the longitudinal nucleation field H n , a magnetization process with a magnetic field applied along the wire axis still consists of nucleation-propagation-annihilation and cannot lead to a multi-domain wire 16 . The second procedure consists in making use of a curved shape, saturating magnetization across the radius, before coming back to remanence.…”
Section: Nucleationmentioning
confidence: 99%